Carbon dioxide adsorption on sawdust biochar - Madzaki, Hazimah; Karim Ghani, Wan A. B.; Rebitanim, Nur Zalikha; Alias, Azil Bahari (Elsevier B.V., 2016)
Biochar has been acknowledged for its unique property which makes it potential candidates as adsorbent for carbon dioxide (CO2) in the flue gas system. In this study, the properties of raw sawdust biochar (SB) and amine treated sawdust biochar (NSB) are being compared. Ultimate analysis was performed using elemental analyzer to determine the carbon, hydrogen, nitrogen and sulfur contents in the adsorbent. Physiochemical characterization has been performed to characterize the biochar properties. Fourier Transform Infrared Spectroscopy (FTIR) and Brunauer-Emmett-Teller (BET) were used to evaluate the functional groups and surface area of the biochar. Thermogravimetric analyzer (TGA) was used to discover the thermal properties, reactivity during adsorption. During the adsorption study, it was observed that raw sawdust biochar gasified at 850 °C gave the highest adsorption of 0.47 kg CO2/kg biochar at temperature of 30 °C. The incorporation of nitrogen functionalities onto the carbon surface may cause decrement of surface area of carbon.